Exploring The Impact Of Temperature Variation On Coconut Seed Oil Yield - Nnadikwe Johnson; Mbadike Columbus Asodike; Iheme Chigozie; Chinemerem Joy johnson (SEAN Institute, 2025)
Coconut oil is a valuable commodity with diverse applications in food, cosmetics, and pharmaceuticals. The extraction process plays a crucial role in determining the quality and yield of coconut oil. Temperature is a critical parameter that affects the efficiency of the extraction process.This study aimed to investigate the effect of temperature on coconut oil extraction using a solvent extraction method, optimizing the extraction process, and providing insights into the relationship between temperature and oil yield. A laboratory-scale solvent extraction method was employed, where coconut oil was extracted from shredded coconut at different temperatures (30°C, 40°C, 50°C, 60°C, and 70°C) using petroleum ether as the solvent. The yield of oil extracted was measured and calculated as a percentage of the initial weight of coconut used.The results showed a significant increase in oil yield with increasing temperature, with the highest yield obtained at 70°C. The yield increased from 26.29% at 30°C to 32.70% at 70°C, indicating a 24.5% increase. The study demonstrates the importance of temperature optimization in coconut oil extraction, providing valuable insights for the industry.This research contributes to the existing body of knowledge on coconut oil extraction, highlighting the potential for process optimization and improved productivity. The findings have important implications for coconut oil manufacturers, providing a basis for the development of more efficient and effective extraction processes.